Nutritional Quality and Safety of Windowpane Oyster Placuna placenta from Samal, Bataan, Philippines - Jessica M. Rustia; Judith P. Antonino; Ravelina R. Velasco; Edwin A. Yates; David G. Fernig (Fishes, 2025)
The windowpane oyster (Placuna placenta) is common in coastal areas of the Philippines, thriving in brackish waters. Its shells underpin the local craft industries. While its meat is edible, only small amounts are consumed locally, most going to waste. Utilization of this potential nutrient source is hindered by the lack of information concerning its organic and mineral content, the possible presence of heavy metal ions, and the risk of microbial pathogens. We report extensive analysis of the meat from Placuna placenta, harvested during three different seasons to account for potential variations. This comprises proximate analysis, mineral, antioxidant, and microbial analyses. While considerable seasonal variation was observed, the windowpane oyster was found to be a rich source of protein, fats, minerals, and carbohydrates, comparing well with the meats of other shellfish and land animals. Following pre-cooking (~90 °C, 25–30 min), the standard local method for food preparation, no viable E. coli or Salmonella sp. were detected. Mineral content was broadly similar to that reported in fish, although iron, zinc, and copper were more highly represented, nevertheless, heavy metals were below internationally acceptable levels, with the exception of one of three samples, which was slightly above the only current standard, FSANZ. Whether the arsenic was in the safer organic form, which is commonly the case for shellfish, or the more toxic inorganic form remains to be established. This and the variation of arsenic over time will need to be considered when developing food products. Overall, the meat of the windowpane oyster is a valuable food resource and its current (albeit low-level) use should lower any barriers to its acceptance, making it suitable for commercialization. The present data support its development for high-value food products in urban markets.

History and Prospects for the Sustainability and Circularity of the Windowpane Oyster Placuna placenta Fishery in the Philippines - Jessica M. Rustia; Judith P. Antonino; Ravelina R. Velasco; Marcelo A. Lima; Edwin A. Yates; David G. Fernig (Fishes, 2023)
The windowpane oyster Placuna placenta lives in brackish coastal waters and has long been economically important to the Philippines because of its durable and translucent shell, which is used as a glass substitute and material for making windowpanes and handicrafts. There has been considerable degradation of the P. placenta fishery over the past decades. Moreover, there are waste and under-exploited by-products, such as the meat, which though nutritious and edible, currently has a very low value; its use is confined to dishes consumed by families in the fishing community. Historically, there have been instances of excellent practice in terms of regulating the P. placenta fishery, while in recent times, there have been local initiatives to restore this and to develop high-value food products from the meat. These initiatives have, however, never been followed through at a provincial or national level. Research on other molluscs and marine organisms highlights that these contain high-value pharmaceutical products, an unexplored facet of P. placenta. This review compiles evidence to establish the groundwork for an essential and comprehensive multidisciplinary research programme centred around the P. placenta, which would ensure a high value for all parts of the oyster, including those currently discarded. By fostering a sustainable and circular economy within this fishery sector and its associated industry, its economic value would be amplified. This is particularly important for oyster harvesters in the Philippines, who often find themselves on the economic ladder’s lower rungs. By integrating the principles of a circular economy, this initiative would not only aim to uplift the economic prospects of these harvesters, but in doing so would drive the restoration of P. placenta to its former range.